EEmergency System to Support Emergency call Evaluation and Ambulance dispatch Procedures - Kyriacou, Efthyvoulos C.; Constantinou, Riana; Kronis, Chris; Hadjichristofi, George; Pattichis, Constantinos S. (My University, 2020)
The main purpose of this study was to create an electronic system (eEmergency system) in order to support, improve and help the procedure of handling emergency calls. An effort to reform the procedures followed for emergency call handling and Ambulance dispatch started on the Island of Cyprus since 2016; along that direction, a central call center was created. The present electronic system was designed for this call center. The main features are the support for ambulance fleet handling, the support for emergency call evaluation and triage procedure and the improvement of communication between the call center and the ambulance vehicles. The main components and the design of this system are outlined in this paper. The part of incident evaluation and ambulance handling, has been in daily practice for more than one year and since then more than 62000 calls were successfully handled and recorded with the use of this system. This system was successfully used from the beginning of the pandemic period of Covid-19.
Keywords: ambulance management; emergency call handling; emergency medical system